Behavioural and neurological symptoms accompanied by cellular neuroinflammation in IL-10-deficient mice infected with Plasmodium chabaudi. (December 2016) - Wilson, Kyle; Stutz, Sonja; Ochoa, Lorenzo; Valbuena, Gustavo; Cravens, Petra; Dineley, Kelly; Vargas, Gracie; Stephens, Robin
Abstract Background Cerebral malaria is one of the most severe complications ofPlasmodium falciparum infection and occurs mostly in young African children. This syndrome results from a combination of high levels of parasitaemia and inflammation. Although parasite sequestration in the brain is a feature of the human syndrome, sequestering strains do not uniformly cause severe malaria, suggesting interplay with other factors. Host genetic factors such as mutations in the promoters of the cytokines IL-10 and TNF are also clearly linked to severe disease.Plasmodium chabaudi, a rodent malaria parasite, leads to mild illness in wildtype animals. However, IL-10−/− mice respond to parasite with increased levels of pro-inflammatory cytokines IFN-γ and TNF, leading to lethal disease in the absence of sequestration in the brain. These mice also exhibit cerebral symptoms including gross cerebral oedema and haemorrhage, allowing study of these critical features of disease without the influence of sequestration. Methods The neurological consequences ofP. chabaudi infection were investigated by performing a general behavioural screen (SHIRPA). The immune cell populations found in the brain during infection were also analysed using flow cytometry and confocal microscopy. Results IL-10−/− mice suffer significant declines in behavioural and physical capacities during infection compared to wildtype. In addition, grip strength and pain sensitivity were affected, suggestive of neurological involvement. Several immune cell populations were identified in the perfused brain on day 7 post-infection, suggesting that they are tightly adherent to the vascular endothelium, or potentially located within the brain parenchyma. There was an increase in both inflammatory monocyte and resident macrophage (CD11bhi, CD45+, MHCII+, Ly6C+/− ) numbers in IL-10−/− compared to wildtype animals. In addition, the activation state of all monocytes and microglia (CD11bint, CD45−, MHC-II+ ) were increased. T cells making IFN-γ were also identified in the brain, but were localized within the vasculature, and not the parenchyma. Conclusions These studies demonstrate exacerbated neuroinflammation concurrent with development of behavioural symptoms inP. chabaudi infection of IL-10−/− animals.